The Effect of Curriculum 13 Implementation on Physical Education Learning Competencies of Elementary School Students During the Covid 19 Pandemic - Fatah, Bagus Ari; Sugiharto, Sugiharto; Ciptaning Wahyu, Imam Santosa (Journal of Physical Education and Sports, 2022)
Research background Implementation of the 2013 curriculum in online physical education learning during the Covid-19 pandemic. The purpose of this study was to examine the effect of applying Curriculum 13 on the enhancement of physical education and physical education learning competencies for primary school children during the COVID-19 pandemic. This investigation was conducted in State Elementary Schools within the Gubug District, Grobogan Regency. The population of all physical education teachers and fifth grade students is 1249 students. The instrument uses a questionnaire questionnaire. Data analysis used descriptive analysis divided into two groups of data, quantitative and qualitative. Statistical analysis included descriptive analysis to calculate the hypothetical mean, standard deviation and frequency distribution (percentage). The results of antecedent research on the completeness of the 2013 curriculum as a means and infrastructure for implementing the 2013 curriculum, as well as learning planning are very good at 100% on the completeness of the curriculum. And good learning planning by 100%. The transaction stage of the learning implementation went well by 60% and the implementation of the authentic assessment went well by 60%. Outcome stage authentic assessment of 49.2% in the good category, 45.4% in the poor category and 0.0% in the very poor category. Only 5.4% of student assessment results are in the very good category. It was found that the implementation of physical education learning with the 2013 curriculum during the covid 19 pandemic still needed recommendations because it had not been able to run optimally.